CO2 EMISSIONS, ENERGY CONSUMPTION AND ECONOMIC GROWTH IN THE USA AND THE UNITED KINGDOM: ARDL APPROACH - Hakan Çetintaş; Murat Sarıkaya (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
This study investigates the effects of energy consumption and the economic growth on the carbon dioxide emissions and causality in a multivariate model, which includes nuclear energy generation, foreign trade and urbanization variables, in the UK and the USA by employing data of 1960-2004. Cointegration test results support that there is a long-term relationship among the variables. While the economic growth in the UK has a positive effect on CO2 emissions in the short term and long term, the economic growth in the USA does not affect CO2 emissions. In both countries, there is a positive relationship between energy consumption and CO2 emissions and a negative relationship between nuclear energy generation and CO2 emissions. There is a unidirectional causality from CO2 to economic growth in the UK and from energy consumption to CO2 emissions in the USA. In both countries, we have detected no causal relationship between energy consumption and the economic growth.